ChemInform Abstract: Soft Ruthenium and Hard Broensted Acid Combined Catalyst for Efficient Cleavage of Allyloxy Bonds. Application to Protecting Group Chemistry. Issue 51 (December 2015) - Tanaka, Shinji; Suzuki, Yusuke; Saburi, Hajime; Kitamura, Masato
Abstract: The facile protocol allows the quantitative removal of allyl protecting group from ethers, esters, carbonates, and carbamates.